Glucose uptake activity of Ganoderma lucidum QRS 5120 in L6 myotube cell - Sharif, Mohd. Faez; Azizan, Nur Hafizah (2023)
The increasing prevalence of diabetes mellitus alongside the advancements in industry and technology underscores the urgency to eliminate this disease. Ganoderma lucidum, renowned for its anti-diabetic, anti-microbial, and anti-inflammatory properties, is widely utilized as a therapeutic medication. The aim of this study was to investigate the glucose uptake activity of exopolysaccharides (EPS) derived from the identified Malaysian Ganoderma lucidum strain QRS 5120 on the L6 myoblast cell line. To achieve this, Ganoderma pellets were cultured using a bioreactor, and EPS were extracted from the pellet for testing its glucose uptake activity. EPS production peak at day 12 (83 g/L) of the cultivation. The extracted EPS underwent a sulfation process to enhance compound solubility and flexibility. This was confirmed by Fourier-transform infrared spectroscopy (FTIR), where sulfation resulted in a sharp vibrational stretch at 1622 cm⁻¹, while unsulfated EPS exhibited a medium stretch at 1632 cm⁻¹. The glucose uptake activity assay revealed that a significantly lower concentration of residual glucose was observed at 500 μg/L (0.43 mg/mL) and 200 μg/L (0.45 mg/mL) when compared to the control group, indicating that EPS has a stimulatory effect on glucose uptake activity in L6 myotube cell lines. Consequently, from this preliminary study, it was shown that the EPS derived from the Malaysian strain Ganoderma lucidum QRS 5120 exhibits glucose uptake activity in skeletal muscle cells.